2022
DOI: 10.1097/md.0000000000028644
|View full text |Cite
|
Sign up to set email alerts
|

Restricted use of copy and paste in electronic health records potentially improves healthcare quality

Abstract: The copy-and-paste feature is commonly used for clinical documentation, and a policy is needed to reduce overdocumentation. We aimed to determine if the restricted use of copy and paste by doctors could improve inpatient healthcare quality. Clinical documentation in an inpatient dataset compiled from 2016 to 2018 was used. Copied-and-pasted text was detected in word templates using natural language programming with a threshold of 70%. The prevalence of copying and pasting after the policy introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(65 reference statements)
0
1
0
Order By: Relevance
“… 140–143 Even though repeating mentions may indicate importance of a finding, duplicating content from previous clinical notes may be used as a shortcut to write clinical notes and result in the generation of clinical notes with redundant text. In current clinical practice, it has already been shown that duplication of clinical note content hinders 144 , 145 clinicians in their day-to-day process when determining the current vs. out-of-date state of patients and may introduce errors that potentially lead to safety issues. 146 Therefore, assessing text redundancy 147 and understanding the effect of note redundancy on developed NLP models are important, as text redundancy can have an impact on model performance.…”
Section: Clinical Applications Of Large Language Models In Cardiologymentioning
confidence: 99%
“… 140–143 Even though repeating mentions may indicate importance of a finding, duplicating content from previous clinical notes may be used as a shortcut to write clinical notes and result in the generation of clinical notes with redundant text. In current clinical practice, it has already been shown that duplication of clinical note content hinders 144 , 145 clinicians in their day-to-day process when determining the current vs. out-of-date state of patients and may introduce errors that potentially lead to safety issues. 146 Therefore, assessing text redundancy 147 and understanding the effect of note redundancy on developed NLP models are important, as text redundancy can have an impact on model performance.…”
Section: Clinical Applications Of Large Language Models In Cardiologymentioning
confidence: 99%
“…This can be done quickly and easily using the copypasting function, ensuring that all relevant information is accurately and securely transferred. Multiple definitions describe copy-pasting, such as copying matching phrases of more than four words or 20 characters between two documents, or a note containing 20% copied text from another document will be considered copying, or 40 identical consecutive words between two documents will be defined as a copy event [8,[11][12][13][14].…”
Section: Copy-pasting Option In Emrsmentioning
confidence: 99%
“…According to a recent study, physicians typically spend 44% of their time on the computer, 26% on clinical documentation, and 18% typing on computers. This significant amount of time could be better spent providing direct patient care [ 13 ]. "Cut-and-paste" refers to cutting text from one location and pasting it into another during manuscript editing or re-writing.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations